Comparison of Growth Performance and Carcass Component Yield of a New Strain of Tom Turkeys to Other Commercial Strains - Roberson, K.D.; Kalbfleisch, J.L.; Dransfield, D. (International Journal of Poultry Science, 2004)
A nineteen week experiment was conducted to evaluate a newly developed strain of toms, (British United Turkeys of America T2), compared to the currently available strains from other genetic sources (Hybrid Converter and Nicholas 700). The T2 strain grew more slowly during the brooding (0 to 5-wk) stage compared to the other two strains. At both slaughter ages (17 and 19 wk), the T2 birds were the heaviest and Nicholas 700 toms were heavier than Hybrid Converter toms. Feed conversion was not significantly different between strains at slaughter ages. Livability was higher for the Hybrid toms compared to the other two strains. Toms were selected for carcass component analysis based upon similar weights across strains at 17 wk and average BW for each strain at 19 wk of age. Regardless of slaughter age, breast yield was higher and thigh and drumstick yield were lower for T2 toms compared to the other two strains. Wing yield was consistently lower and breast skin was higher for Hybrid toms. Mortality due to cardiovascular disease was higher for Nicholas 700 toms due primarily to round heart incidence from 2 to 5 wk of age. The T2 tom strain reached market weight earlier and yielded more premium priced meat than other commercial strains at heavy market weights.